ASSESSMENT OF SYMPTOMATIC DIABETIC PATIENTS WITH NORMAL NERVE CONDUCTION STUDIES: UTILITY OF CUTANEOUS SILENT PERIODS AND AUTONOMIC TESTS - İŞAK, BARIŞ; ULUÇ, KAYIHAN; KAHRAMAN KOYTAK, PINAR; TANRIDAĞ, TÜLİN (WILEY, 2011)
Established electrophysiological methods have limited clinical utility in the diagnosis of small-fiber neuropathy (SFN). In this study, diabetic patients with clinically diagnosed SFN were evaluated with autonomic tests and cutaneous silent periods (CSPs). Thirty-one diabetic patients with clinically suspected SFN and normal nerve conduction studies were compared with 30 controls. In the upper extremities (UE), the CSP parameters did not differ statistically between the patient and control groups, whereas, in the lower extremities (LE), patients had prolonged CSP latencies (P = 0.018) and shortened CSP durations (P < 0.001). The sensitivity of the CSP duration was 32.6%, and the specificity was 96.7%. The expiration-to-inspiration ratios and amplitudes of the sympathetic skin responses in the lower extremities were also reduced. Our findings indicate that the diagnostic utility of CSPs was higher than that of the autonomic tests to support the clinically suspected diagnosis of SFN. Muscle Nerve 43: 317-323, 2011
Keywords: autonomic tests; cutaneous silent period duration; diabetes mellitus; interneuron; small-fiber neuropathy; SMALL-FIBER NEUROPATHY; SYMPATHETIC SKIN-RESPONSE; SUDOMOTOR; CRITERIA; PROFILE; PLANTAR; BIOPSY